HUBUNGAN KEBIASAAN KONSUMSI MAKANAN KARIOGENIK DAN STATUS SOSIAL EKONOMI DENGAN KEJADIAN KARIES GIGI PADA ANAK KELAS 1 DI SDN 2 GUNUNGMASIGIT KABUPATEN BANDUNG BARAT - Febrianty, Fitria; Widyastuti, Tri; Supriyanto, Irwan; Chaerudin, Denden Ridwan (Jurnal Terapi Gigi dan Mulut, 2023)
Background: Dental caries is a common dental and oral health disease found in the community. Dental caries can arise from the consumption of cariogenic foods in large quantities and an attitude that does not pay attention to dental and oral hygiene. Dental caries disease is often experienced in developing countries because socioeconomic status affects the quality of health. Objective: To determine the relationship between cariogenic food consumption habits and socioeconomic status with the incidence of dental caries in grade 1 children at SDN 2 Gunungmasigit, West Bandung Regency. Methods: This study used an analytical survey method with a cross sectional design. The sample of this study was 32 people determined by the Simple Random Sampling technique. Data analysis used Fisher Exact Test. Results: There is a relationship between cariogenic food consumption habits and the incidence of dental caries (p value = 0.024<0.05), and there is a relationship between socioeconomic status and the incidence of dental caries (p value = 0.008<0.05). Conclusion: There is a relationship between cariogenic food consumption habits and socioeconomic status with the incidence of dental caries in grade 1 children at SDN 2 Gunungmasigit, West Bandung Regency.